"I shouldn't have gotten out of there! I like to study!”: The challenges of people with Autism Spectrum Disorder for schooling (Research, Society and Development, 2021)
This study analyzed the school experiences of adult people with Autism Spectrum Disorder (ASD) to evidence aspects that enhanced them and/or weakened them in the continuation or interruption of schooling. Vygotski's historical-cultural approach constituted the theoretical contribution of this research, which used the narrative of life and had as unit of analysis the category of experience. The study involved four individuals oralized, aged between 30 and 36 years, three male and one female, in the municipality of Maceió-Alagoas-Brazil. The data were produced from narrative interviews, and, given the diversity of the communicative skills of people with ASD, the Alternative Communication System for Literacy of People with Autism (SCALA) was used, a technology assisted, in a supplementary way, from its Visual Narratives module to construct the stories of their school spaces. It was found that the participants experienced the weaknesses of the school system to deal their specificities and that the experiences in school spaces reflected in their schooling, with impacts on development, constitution, social position and appropriations and activities in the world. However, the potentialities of the mobilization of mothers for school and social inclusion constituted their foundations of life. Since the participants with ASD were part of the Social Situation of Development (SSD) and their relations with the environment, the situations and events experienced influenced the psychological development and were guiding them in their positions and personal characteristics.